2020
DOI: 10.1088/1742-6596/1529/5/052019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cognitive and metacognitive strategies on learning performance in digital learning: What’s working and what’s not in the age of brilliant technology

Abstract: Ineffective cognitive processes result in learning difficulties online. Hence, how cognitive learning processes influence the way students engage and learn online needs further investigation. This study, therefore, examined cognitive engagement and metacognitive knowledge strategies on learning performance among Malaysian IT Undergraduates. A sample of 563 IT undergraduates from private higher education in Malaysia participated in this quantitative study that were collected through a questionnaire. Data was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Murphy (2020) presents an exploration focused on the symbiotic connection between Informatics and eLearning that leads to contemporary and innovative solutions, facilitating and automating a wide variety of activities at information processing. Anthonysamy et al (2020) promote a special type of software called Algodoo that present three types of activity that have observed during students' free exploration, which allows students to explore a range of physics phenomena within the same digital learning environment. And in another study, Blake et al (2020) promote the most popular eLearning educational platform, Moodle-LMS (collaborative platform of Google and Microsoft) in Romanian universities, which contain mail group modules, virtual classes, video conferencing, presentation and testing.…”
Section: The Literature Reviewmentioning
confidence: 99%
“…Murphy (2020) presents an exploration focused on the symbiotic connection between Informatics and eLearning that leads to contemporary and innovative solutions, facilitating and automating a wide variety of activities at information processing. Anthonysamy et al (2020) promote a special type of software called Algodoo that present three types of activity that have observed during students' free exploration, which allows students to explore a range of physics phenomena within the same digital learning environment. And in another study, Blake et al (2020) promote the most popular eLearning educational platform, Moodle-LMS (collaborative platform of Google and Microsoft) in Romanian universities, which contain mail group modules, virtual classes, video conferencing, presentation and testing.…”
Section: The Literature Reviewmentioning
confidence: 99%
“…It plays key role in classroom learning such as creative thinking (Jia et al, 2019), task completion and learning outcomes (Stanton et al, 2021), and academic performance (Biggs, 1988;Norehan, 2009). The psychologists and authors in their study, showed that students' metacognitive learning strategies improve cognitive performance, academic achievement, and problem solving (Anthonysamy et al, 2020;Djudin, 2017;Stephanou & Karamountzos, 2020). According to (Flavell, 1979;Tarricone, 2011) metacognition is an ability to recognize own cognitive knowledge and regulate the cognitive knowledge in daily learning tasks.…”
Section: Introductionmentioning
confidence: 99%